1986
DOI: 10.1111/j.1365-2125.1986.tb05210.x
|View full text |Cite
|
Sign up to set email alerts
|

Slow release nifedipine and atenolol as initial treatment in blacks with malignant hypertension.

Abstract: We have compared the efficacy and safety of slow release nifedipine and atenolol given orally as initial treatment for malignant hypertension. Twenty consecutive black patients with untreated malignant hypertension, whose diastolic pressure remained greater than 120 mm Hg after 3 h bed rest, were randomized to receive either slow release nifedipine 40 mg at 1 and 12 h, or atenolol 100 mg at 0 h only. Patients remained supine throughout the study. Blood pressure was measured using a semi‐automatic recorder (Ome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…19 It is thus likely that the reported difference was unrelated to the use of a specific /3-adrenergic receptor blocker. Likewise the less satisfactory response to A agrees with the well-documented poor efficacy of various /3-adrenergic receptor blocking agents in hypertensive blacks when used as monothera p V 20-26 jjj contrast to the current findings, one study 27 has recently reported similar blood pressure reduction after acute oral administration of A (100 mg) and slowrelease nifedipine in South African blacks with malignant hypertension and high PRA that could have modulated the antihypertensive response to the administered drugs. It has been shown that /3-adrenergic receptor blockers are more efficient the higher the renin, whereas the opposite is true for calcium entry blockers.…”
Section: Discussionsupporting
confidence: 84%
“…19 It is thus likely that the reported difference was unrelated to the use of a specific /3-adrenergic receptor blocker. Likewise the less satisfactory response to A agrees with the well-documented poor efficacy of various /3-adrenergic receptor blocking agents in hypertensive blacks when used as monothera p V 20-26 jjj contrast to the current findings, one study 27 has recently reported similar blood pressure reduction after acute oral administration of A (100 mg) and slowrelease nifedipine in South African blacks with malignant hypertension and high PRA that could have modulated the antihypertensive response to the administered drugs. It has been shown that /3-adrenergic receptor blockers are more efficient the higher the renin, whereas the opposite is true for calcium entry blockers.…”
Section: Discussionsupporting
confidence: 84%
“…The blood pressure should be carefully and gradually lowered because a rapid reduction of blood pressure can cause ischemia of target organs. Most patients can be managed with oral antihypertensive therapy [3,4]. Combination therapy with arotinolol and extended-release nifedipine may be beneficial for the improvement of renal impairment and cardiac damage in patients with malignant-phase hypertension [5].…”
Section: Discussionmentioning
confidence: 99%
“…The plasma renin activity (PRA) and plasma aldosterone concentration (PAC) were both significantly elevated (PRA 8.1 ng/mL/h, PAC 533 pg/mL). The blood gas examination revealed alkalosis with a decreased PCO 2 level and a normal range of HCO 3 -(pH 7.474, PCO 2 32.7 mmHg, PO 2 64.4 mmHg, HCO 3 -23.4 mEq/L, sodium 132 mEq/L, potassium 2.4 mEq/L, chloride 95 mEq/L, anion gap 13.6 mEq/L). These findings suggested the existence of metabolic alkalosis due to secondary hyperaldosteronism, in addition to respiratory alkalosis.…”
Section: Case Reportmentioning
confidence: 98%
“…atenolol 50-100mg) are effective therapy for the reduction in blood pressure in hypertensive emergencies. 7 They need to be used with caution in patients with evidence of pulmonary oedema or left ventricular dysfunction, as they may cause worsening of symptoms.…”
Section: Beta Blockersmentioning
confidence: 99%